Genomic Characterization of Antibiotic Resistant Escherichia coli Isolated From Domestic Chickens in Pakistan - Rafique, Muhammad; Potter, Robert F.; Ferreiro, Aura; Wallace, Meghan A.; Rahim, Abdul; Ali Malik, Akbar; Siddique, Naila; Abbas, Muhammad Athar; D’Souza, Alaric W.; Burnham, Carey-Ann D.; Ali, Naeem; Dantas, Gautam (Frontiers in Microbiology, 2020)
Poultry husbandry is important for the economic health of Pakistan, but the Pakistani poultry industry is plagued by infections from Escherichia coli. We performed Illumina whole genome sequencing on 92 E. coli isolates obtained from the livers of deceased chickens originating in five Pakistani geographical regions. Our analysis indicates that the isolates are predominantly from the B1 and A clade and harbor a diverse number of antibiotic resistance and virulence genes, with no linkage between phylogeny and antibiotic resistance gene presence but some association between phylogeny and virulence gene and SNP presence for the B1 and E phylogroups. Alarmingly, 82/92 of the E. coli strains characterized in this study are multidrug resistant with 100% (92/92) resistance to linomycin, 81.5% (75/92) to streptomycin, 79.3% (73/92) to ampicillin and 66.3% (61/92) to ciprofloxacin. These results provide a high-resolution analysis of poultry-associated E. coli isolates in an area with a high endemic burden of antibiotic resistance. Surveillance of antibiotic resistance in poultry associated E. coli isolates is an important pillar of the One Health concept to integrate analysis of potential pathogens in human, animal, and environmental niches.